Snapping Pes Syndrome after Unicompartmental Knee Arthroplasty - Inui, Hiroshi (Knee Surg Relat Res, 2016)
Snapping pes syndrome is defined as a snapping sensation in the medial knee caused by pes anserinus and rarely occurs. Snapping pes syndrome after unicompartmental knee arthroplasty (UKA) has not been reported yet. We experienced two cases with this syndrome after UKA. Conservative treatment was effective in one case, while surgical excision of the gracilis tendon was necessary to relieve painful snapping in the other case. The main cause of the first case might be posteromedial overhang of the tibial tray that reached up to 5 mm. The probable cause of the second case was posteromedial overhang of the mobile bearing.